Mutiple Ionization of Rare Gases by Electron Impact - Krauss, M. (J Res Natl Bur Stand A Phys Chem, 1959)
Electron impact studies of multiple ionization processes in helium, neon, argon, and xenon appear to support theoretical conclusions that the threshold probability for n-fold ionization is proportional to the nth power of the electron energy in excess of the threshold energy. The probability law applies, for the cases studied, over a considerable energy range that, for all but He(2+), includes the possible onset of more than one mode of ionization. The presence of a Boltzmann spread in the energy of the electron beam or specific focusing effects due to ion source geometry are found to affect only the foot of the probability curve. By the use of certain assumptions, an estimate is also made of the departure from a (3)P ionization probability curve resulting from onset of ionization to the (1)D and (1)S states.